2014
DOI: 10.1016/j.ijsu.2014.08.350
|View full text |Cite
|
Sign up to set email alerts
|

Pathophysiology, clinical presentation and management of diversion colitis: A review of current literature

Abstract: The clinical presentation of diversion colitis varies significantly. In symptomatic patients short chain fatty acid enema may help. Further prospective studies are required for evaluation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
42
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(46 citation statements)
references
References 37 publications
3
42
0
1
Order By: Relevance
“…The incidence has been described to vary between 50% and 91% [ 3 5 ]. Although the majority of patients do not suffer from clinical symptoms, up to 40% of affected patients report clinical symptoms including mucous discharge, abdominal pain, bleeding, and tenesmus [ 1 , 5 , 23 ]. Severe clinical courses have been described sporadically [ 3 , 24 , 25 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The incidence has been described to vary between 50% and 91% [ 3 5 ]. Although the majority of patients do not suffer from clinical symptoms, up to 40% of affected patients report clinical symptoms including mucous discharge, abdominal pain, bleeding, and tenesmus [ 1 , 5 , 23 ]. Severe clinical courses have been described sporadically [ 3 , 24 , 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…Severe clinical courses have been described sporadically [ 3 , 24 , 25 ]. However, symptoms can persist even after reversal of fecal diversion and negatively affect the quality of life [ 5 , 23 , 26 ]. In patients where reestablishment of intestinal continuity is not feasible, surgical resection of the dysfunctioned bowel segment may be necessary when medical anti-inflammatory treatment fails.…”
Section: Discussionmentioning
confidence: 99%
“…L-Glutamine is a fuel source for the epithelial cells of colon [ 3 , 4 , 7 ]. It is an essential precursor for nucleic acid bio-synthesis and is therefore essential for proliferation of cells with rapid turnover such as the intestinal mucosa.…”
Section: Discussionmentioning
confidence: 99%
“…SCFA are produced by fermentation of fibers. Thus fibers act as a substrate to provide the colonocytes a fuel source in the form of SCFA [ 1 , 3 ]. The present study has found that there was no significant difference in epithelial cell height and mucosal thickness of Group III that received Psyllium.…”
Section: Discussionmentioning
confidence: 99%
“…This is important to protect the gut barrier, reduce bacterial translocation, and even decrease the morbidity and mortality by reducing the septic complications. PDLI can manage the diversion proctocolitis by antegrade succus entericus reinfusion, which may also prevent the colonic complications such as diarrhea, obstruction, missing colon fistula and stenosis after performing closure of the stoma [38,39]. PDLI could decrease the rate of reoperation, the hospitalization time and cost of hospitalization.…”
mentioning
confidence: 99%